The Effect of Web-Enhanced Learning Activities (WELA) on the Achievement in English of First Year High School Students - Bustos, Katherine Faith M. (JPAIR Multidisciplinary Research, 2010)
The study was conducted to verify the effects of Web-Enhanced Learning Activities (WELA) on the achievement in English of first year high school students. The research combined the quantitative approach using the quasi-experimental design, with the qualitative approach involving immersion learning. A total of 66 respondents from the two first year classes, 34 under the experimental group and 32 under the control group, were used as subjects of the study. Results indicate no significant difference between the experimental and control groups in pretest scores but show significant difference in posttest scores. While the respondents gained knowledge in both approaches, students under the WELA displayed higher achievement level in the posttest, significantly outperforming the students in the control group. Moreover, the following positive behaviors were observed among the students under the WELA: (a) increased interaction among the students, between the students and learning materials, and between the students and the teacher; (b) decrease of absenteeism cases; (c) independent learning; (d) enhanced and structured learning styles; and (e) more defined focus in learning. The WELA clearly appears to be very effective approach in enhancing English achievement levels of first year students.